O crime de estupro virtual : (des) necessidade de tipificação pelo ordenamento jurídico brasileiro - Marodin, Tayla Schuster (2021)
This dissertation addresses a new conduct that has been framed in the criminal type of rape, arising from Law 12,015 / 2009, which ended up considering in the same article the carnal conjunction as other acts against sexual freedom. The new conduct brought, understood by virtual rape, raised many doubts about the proper application of the law in this type of situation. Therefore, the objective of this work is to analyze the need or not of typification by the Brazilian legal system of virtual rape. The work has the structure of three chapters, the first of which is introductory to the concepts of virtual crimes and the emergence of the internet; the second brings the amendments to Law 12,015 / 2009, as well as the intention of the legislator with the referred changes; and the third focused exclusively on the analysis of the crime of virtual rape and the typical nature of the conduct, also analyzing the principle of legality. It is analyzed in the course of the work that there are different positions, and some believe that the configuration of this crime can occur in articles 213 and 217-A, while on the other hand and mostly, they understand that to have the crime configured, physical contact is necessary . Therefore, through technology and virtual crimes, a survey was carried out on the possibility of being framed by virtual rape, in order to understand the need or not of physical presence. It was possible to conclude with this work that the virtual environment is just an instrument that can be used to arrive at the commission of the crime of rape, since the physical presence of the subject is necessary to configure such a crime. For this reason, it is disproportionate to accept the custodial sentence for any and all cases that may be understood as virtual rape.